Model Pengajaran Alkitab dalam Pendidikan Kristen di Era Digital - Eriyani Mendrofa (STIPAK Malang, 2021)
The development of increasingly advanced technology in the modern era is an opportunity for the ease of preaching God's word with digital media. The problem is that there are still many teachers, be they lecturers, teachers, or servants of God, who do not really understand the benefits of mastering technology as a vehicle for God's word. In this paper, the author will present a new challenge for the Christian world to face increasingly sophisticated technology. Using a descriptive qualitative method with a literature study approach. Thus, it can be concluded that the teaching of the Bible in Christian education in the Digital Age is. First, the basis and calling of teaching according to the Bible; second, the role of Information Technology as an Educational Media. And learn from the actualization of Jesus' ministry as an Example in Teaching. Moreover, relying on the role of the Holy Spirit as the only teacher for the needs of society in the modern era. AbstrakPerkembangan teknologi yang semakin maju di era modern merupakan peluang bagi kemudahan pemberitaan firman Tuhan dengan media digital. Permasalahannya masih banyak pengajar baik itu dosen, guru, atau para pelayan Tuhan yang belum terlalu mengerti manfaat menguasai teknologi sebagai kendaraan bagi firman Tuhan. Dalam tulisan ini, penulis akan menyajikan tantangan baru bagi dunia kekristenan untuk menghadapi teknologi yang semakin canggih. Menggunakan metode kualitatif dekritif dengan pendekatan syudi literature. Dengan demikian dapat disimpulkan bahwa pengajaran Alkitab dalam pendidikan Kristen di Era Digital adalah. Pertama, dasar dan panggilan pengajaran menurut Alkitab, kedua mendeskripsikan peran Teknologi Informasi sebagai Media Pendidikan. Serta belajar dari aktualisasi pelayanan Yesus sebagai Teladan dalam Mengajar. Terlebih mengadalkan peran Roh Kudus sebagai satu-satunya Pengajar bagi kebutuhan masyarakat di era modern.